2013
DOI: 10.1890/12-1727.1
|View full text |Cite
|
Sign up to set email alerts
|

Food‐web dynamics in a large river discontinuum

Abstract: Abstract. Nearly all ecosystems have been altered by human activities, and most communities are now composed of interacting species that have not co-evolved. These changes may modify species interactions, energy and material flows, and food-web stability. Although structural changes to ecosystems have been widely reported, few studies have linked such changes to dynamic food-web attributes and patterns of energy flow. Moreover, there have been few tests of food-web stability theory in highly disturbed and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
200
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(210 citation statements)
references
References 136 publications
(131 reference statements)
9
200
0
1
Order By: Relevance
“…More detailed crocodile surveys are needed to estimate the total number of wildebeest that may be consumed by crocodiles in the Mara River during the migration period. These data suggest that consumption by fish and other aquatic animals may be an important pathway for wildebeest carcasses, although further analysis of secondary production is needed to quantify this pathway (38). Moreover, pulsed inputs of wildebeest carcasses may influence the river food web at decadal time scales through the contribution of bone to basal resources.…”
Section: Significancementioning
confidence: 97%
“…More detailed crocodile surveys are needed to estimate the total number of wildebeest that may be consumed by crocodiles in the Mara River during the migration period. These data suggest that consumption by fish and other aquatic animals may be an important pathway for wildebeest carcasses, although further analysis of secondary production is needed to quantify this pathway (38). Moreover, pulsed inputs of wildebeest carcasses may influence the river food web at decadal time scales through the contribution of bone to basal resources.…”
Section: Significancementioning
confidence: 97%
“…Similarly, within the Colorado River near the confluence with the Little Colorado River, Finch et al (2015) estimated juvenile Humpback Chub abundance during 2009-2011 and found the highest abundance in 2011, despite finding no changes in condition. Cross et al (2011) documented that prey consumption rates by fishes in the Colorado River nearly equaled or exceeded invertebrate production, which may cause food limitation that could lead to lower condition. We were only able to estimate length-weight relationships for 1 y (2011) during the time period Van Haverbeke et al (2013) noted increasing abundance for Humpback Chub; but in this one year Humpback Chub showed the most robust size for a given length of all the years we examined (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Addition, dam construction and operation can make a substantial contribution to ecosystem hazards, things like loss of forests and wildlife habitats, loss of aquatic diversity, including upstream and downstream fisheries, interruption of fish migration and loss of the services of downstream wetlands, riverine and estuarine ecosystems [40,41]. Ecologically, dams have the ability to change river's physicochemical characteristics that are the major reasons for change in the aquatic communities structure [42].…”
Section: The Ba Lai Dam May Be Reasons For Cause the Nematode Distribmentioning
confidence: 99%